2021
DOI: 10.1097/md.0000000000027708
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrasound-guided low serratus anterior plane block on laparoscopic cholecystectomy postoperative analgesia

Abstract: Background:Anterior serratus plane block for analgesia in many procedures, but there have been no reports of analgesia undergoing laparoscopic cholecystectomy (LC). We investigated the effects of ultrasonic-guided low serratory anterior block on patients undergoing LC.Methods:One hundred patients who undergo LC were selected and randomly divided into 2 groups: Patients in group C with routine general anesthesia and patients in group S treat low anterior serratus block combined with general anesthesia. The serr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Propofol is an ultra-short-acting intravenous anesthetic with high lipid solubility and almost insoluble in water. Due to its rapid onset of action, rapid and stable recovery of patients, with slight discomfort after recovery, it has been well-recognized in clinical practice [15]. e molecule of the new ultra-short-acting opioid, remifentanil, contains an ester bond, and its drug is mainly hydrolyzed by nonspecific esterases, resulting in the drug metabolism insusceptible to liver and kidney functions [16].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is an ultra-short-acting intravenous anesthetic with high lipid solubility and almost insoluble in water. Due to its rapid onset of action, rapid and stable recovery of patients, with slight discomfort after recovery, it has been well-recognized in clinical practice [15]. e molecule of the new ultra-short-acting opioid, remifentanil, contains an ester bond, and its drug is mainly hydrolyzed by nonspecific esterases, resulting in the drug metabolism insusceptible to liver and kidney functions [16].…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 29 Additionally, it has been shown that the utilization of low SAP block can provide a good analgesic effect and reduce opioid consumption in liver surgery and laparoscopic cholecystectomy. 17 , 18 Thus, we speculate that the ultrasound-guided bilateral low DSAP blocks can improve the quality of recovery and provide an efficient analgesic effect for patients undergoing TRT.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have demonstrated the good analgesic efficacy of low SAP block in laparoscopic cholecystectomy and hepatectomy. 17 , 18 However, the efficacy of bilateral low SAP blocks analgesia in the patients undergoing TRT remains unknown. Whether a relationship exists between bilateral low SAP blocks and postoperative recovery quality is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Low SAPB (T8–T9) will be performed bilaterally on each patient by experienced anesthesiologists under ultrasound guidance after anesthesia induction. 16 The linear ultrasound transducer (8–12 MHz) will be placed over the mid-clavicular region of the thoracic cage in a sagittal plane, with the patients in the supine position. The ribs will be counted inferiorly and laterally.…”
Section: Methodsmentioning
confidence: 99%
“… 15 The application of low SAPB has been demonstrated to reduce opioid consumption and increase patient’s satisfaction with postoperative analgesia in liver surgery and laparoscopic cholecystectomy. 16 , 17 However, the efficacy of low SAPB analgesia in the patients undergoing TRT is unclear and has never been described in scientific literature.…”
Section: Introductionmentioning
confidence: 99%